IMPACT OF THE GOVERNMENT’S HOUSE ASSISTANCE ON CHANGES IN SPATIAL PATTERNS AND COMMUNITY BEHAVIOR OF PINGGAN TRADITIONAL VILLAGE, BANGLI BALI REGENCY - Putra, A.A. Gde Oka; Widnyana, I Ketut; Vipriyanti, Nyoman Utari (International Journal of Research -GRANTHAALAYAH, 2021)
Pinggan Village, which is an ancient traditional village (Bali Aga) with a pattern of settlements and traditional mountainous Balinese buildings, namely Bale Saka Roras, in 2018 received assistance to improve housing quality from the government. that. This study aims to determine and analyze the impact of housing assistance on changes in settlement space patterns and changes in local community behavior. Research for changes in spatial patterns is descriptive qualitative, and changes in behavior using the two-average difference test analysis method. The results showed that housing assistance had an effect on changes in spatial patterns on the macro and meso scales, as well as changes in the behavior of rural communities. The meso scale is seen in changes in the shape and addition of buildings to the yard, while on a macro scale the distribution of housing assistance forms new settlement groups outside the traditional village area. Behavioral changes that occur are the decreasing function of traditional buildings (bale’s sake roras) only for religious and cultural activities.